Direct ink writing of Bi2Te3-based thermoelectric materials induced by rheological design. (January 2023) - Wang, Zhengshang; Cui, Wen; Yuan, Hao; Kang, Xiaoli; Zheng, Zhou; Qiu, Wenbin; Hu, Qiujun; Tang, Jun; Cui, Xudong
Abstract: Waste heat recovery systems built with thermoelectric (TE) materials offer promising means to generate electricity from waste heat directly, if TE materials or devices with controllable shapes are created through direct ink writing. However, the nature of TE inks used for direct ink writing must be modified with appropriate rheology to maintain stability and facilitate extrusion, as well as proper mechanical properties to resist deformation. Here, we report Bi2 Te3 -based inks modified with additives that allow direct printing of tunable architectures. The polyelectrolyte additives-induced adsorbed layers on the surface of TE particles are shown to significantly improve the stability and viscoelasticity of inks. Besides, the improved inks modified with methylcellulose additives exhibit an apparent enhancement of strength properties, thereby enabling the predesigned shapes to hold the successive layers printed above. Using charge control and framework reinforcement, the Bi2 Te3 -based inks print a series of architectures with porous structures, which largely reduce thermal conductivities. As a result, our three-dimensional-printed materials display high figures of merit ZT of 0.65 and 0.53 for p- and n-type. This work explores how additives can influence both rheological properties, printability, and microstructures, which pave the way to construct complex architectures and improve TE performance for structural and functional applications. Graphical abstract: Image 1 Highlights: Bi2 Te3 -based inks modified with additives allow printing of tunable architectures. Rheological design optimizes the composition of inks and printability. Methylcellulose in the inks triggers the increase of strength and stability. Porous structures in the printed samples enhance the thermoelectric performance.